(3xy - 1) (4xy + 2)
Question
Updated 7/27/2016 8:55:04 PM
Edited by jeifunk [7/27/2016 8:54:28 PM]
s
Original conversation
User: (3xy - 1) (4xy + 2)

Weegy: (3xy - 1) (4xy + 2)
= 12x^2y^2 + 6xy - 4xy - 2
= 12x^2y^2 + 2xy - 2
Andrew.|Points 63932|

User: [4 - (3c - 1)][6 - ( 3c - 1)]

User: (a - b)(a 2 + ab + b 2)

Question
Updated 7/27/2016 8:55:04 PM
Edited by jeifunk [7/27/2016 8:54:28 PM]
Rating
3
[4 - (3c - 1)][6 - ( 3c - 1)] = 9c2 - 36c + 35
3
(a - b)(a^2 + ab + b^2) = a^3 - b^3

Questions asked by the same visitor
How many people in the world speak Spanish?
Question
Updated 7/20/2016 4:16:10 PM
427 million people in the world speak Spanish.
Confirmed by jeifunk [7/20/2016 4:16:05 PM]
(3xy - 1) (4xy + 2)
Weegy: (3xy - 1) (4xy + 2) = 12x^2y^2 + 6xy - 4xy - 2 = 12x^2y^2 + 2xy - 2 User: (2x - 3y)(4x - y) Weegy: (2x - 3y)(4x - y) = 8x^2 - 2xy - 12xy + 3y^2 = 8x^2 - 14xy + 3y^2 User: (x + y + 3)(x + y - 4) User: (ab - 9)(ab + 8) Weegy: (ab + 3)(ab - 3) = a^2b^2 - 3ab + 3ab - 9; = a^2b^2 - 9 User: (m 3 n + 8)(m 3 n - 5) Weegy: (n + 8)(n - 2) = n^2 - 2n + 8n - 16; = n^2 + 6n - 16 User: (a + 3)(a - 2) User: (1 - 7x)(1 + 9x) User: (x 2 + 2x - 1)(x 2 + 2x + 5) Weegy: (x^2 + 2x - 1)(x^2 + 2x + 5) = x^4 + 2x^3 + 5x^2 + 2x^3 + 4x^2 + 10x - x^2 - 2x - 5; = x^4 + 4x^3 + 8x^2 + 8x - 5 User: [4 - (3c - 1)][6 - ( 3c - 1)] Weegy: 3-3 = 0 (More)
Question
Updated 7/27/2016 9:01:29 PM
(x + y + 3)(x + y - 4) = x2 + 2xy + y2 - x - y - 12
(ab - 9)(ab + 8)
=a^2b^2 + 8ab - 9ab - 72
=a^2b^2 - ab - 72
(m^3 n + 8)(m^3n - 5)
=m^6n^2 - 5m^3n + 8m^3n - 40
=m^6n^2 + 3m^3n - 40
(a + 3)(a - 2)
=a^2 - 2a + 3a - 6
=a^2 + a - 6
(1 - 7x)(1 + 9x)
= 1 + 9x - 7x - 63x^2
= - 63x^2 + 2x + 1
Find the sum of (5x3 + 3x2 - 5x + 4) and (8x3 -5x2 + 8x + 9).
Weegy: (5x3 + 3x2 - 5x + 4) + (8x3 -5x2 + 8x + 9) = 13x^3 2x^2 + 3x + 13 User: Simplify 8 - (-5) - 4(-7). User: Simplify 2(x - 4) + 7(x + 2). User: 6x 4 + 15x 3 y 2 + 3x 2 y 3 User: (5x2 - 7)(5x2 + 7) Weegy: (5x^2 - 7)(5x^2 + 7) = 25x^4 + 35x^2 - 35x^2 - 49; = 25x^4 - 49 User: 9x 2 - 18x - 7 ÷ (3x + 1) (More)
Question
Updated 7/27/2016 9:21:00 PM
(9x^2 - 18x - 7) ÷ (3x + 1)
= (3x + 1)(3x - 7)/ 3x + 1
= 3 - 7
2(x - 4) + 7(x + 2)
= (2x + 7x) + (-8 + 14)
= 9x + 6
6x^4 + 15x^3 y^2 + 3x^2 y^3 = 15x^3y^2 + 3x^2y^3 + 6x^4
32,269,240
Popular Conversations
Egyptians used the Nile to __________ ...
I didn’t do my homework; consequently, I did not get credit for the ...
Weegy: The movie was really bad; therefore, many people left early.
The effort made by the mother's body to move the baby from the uterus ...
Weegy: The effort made by the mother's body to move the baby from the uterus and through the birth canal is called ...
Everyone in the Security Council has veto power. True False
Weegy: A veto is the power to unilaterally stop an official action, especially the enactment of legislation. User: ...
GET
GET THE APP.
weegy* *
Get answers from Weegy and a team of really smart live experts.
S
L
P
L
P
P
Points 1441 [Total 9541] Ratings 0 Comments 1441 Invitations 0 Offline
S
L
P
R
P
R
L
P
P
C
R
P
R
L
P
R
P
R
Points 1423 [Total 15178] Ratings 7 Comments 1333 Invitations 2 Online
S
L
Points 1376 [Total 1745] Ratings 0 Comments 1376 Invitations 0 Offline
S
L
P
1
L
Points 1151 [Total 5434] Ratings 10 Comments 1051 Invitations 0 Offline
S
L
L
1
Points 659 [Total 6575] Ratings 6 Comments 599 Invitations 0 Offline
S
L
P
P
P
1
P
L
Points 636 [Total 8087] Ratings 15 Comments 486 Invitations 0 Offline
S
L
Points 451 [Total 482] Ratings 0 Comments 1 Invitations 45 Offline
S
L
1
Points 286 [Total 4290] Ratings 9 Comments 196 Invitations 0 Offline
S
L
Points 282 [Total 2816] Ratings 3 Comments 252 Invitations 0 Offline
S
L
Points 229 [Total 314] Ratings 1 Comments 219 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.